Perforated Liver Abscess in Makkah, Saudi Arabia: A Case Report - Alsaud, Reham Nasser; Alserifi, Malik Mohammad; Alqithami, Heba Badi; balubaed, Jihad khaled; Alaryni, Abdulrahman; Ashour, Mohammed Fahad (Journal of Posthumanism, 2025)
Pyogenic liver abscess (PLA) is a significant cause of hospitalization and potentially fatal conditions in low-income nations. Most pyogenic abscesses are polymicrobial and make up about 80% of all liver abscesses in the developed world. One major complication that might negatively affect a patient's life is the rupture of a pyogenic liver abscess (PLA). In this case, we report a rare case presented by pneumoperitoneum due to a ruptured pyogenic liver abscess in an undiagnosed type 1 DM caused by Klebsiella pneumoniae. A 25-year-old Yamni male patient, not known to have any medical illness and surgical free, came to the emergency department complaining of right-sided abdominal pain for 10 days.The result of a computed tomography (CT) scan revealed a ruptured hepatic abscess in segment VI of the liver (11×10×10 cm) with gas formation, marked free fluid in the abdomen, and pneumoperitoneum. The patient underwent an exploratory laparotomy. Klebsiella pneumoniae was demonstrated by blood culture and fluid culture. His postoperative course was complicated by diabetic ketoacidosis, hypoglycemia-induced seizures, and multiple ICU admissions. Despite these challenges, with surgical intervention, antibiotic therapy, drainage procedures, and diabetes management, the patient made a significant recovery. Three months post-surgery, he remains stable and under regular outpatient follow-up. The majority of acute abdominal pain cases accompanied by pneumoperitoneum are caused by a perforated hollow viscus. But it's also necessary to consider alternative possibilities, such as the gas-forming bacteria rupturing the liver abscess.